2015
DOI: 10.1016/j.chb.2015.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Using virtual presence and survey instructions to minimize careless responding on Internet-based surveys

Abstract: WARD, MARY KATHRINE. Using Virtual Presence and Survey Instructions to Minimize Careless Responding on Internet-Based Surveys. (Under the direction of Dr. Samuel B. Pond.) Internet-based survey data inform knowledge creation in research and justify work activities in many organizations. While there are decided advantages to Internet-based surveys, this mode of administration comes with its own set of challenges. Survey respondents may intentionally or unintentionally respond to the survey in a manner that does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
73
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 43 publications
(8 reference statements)
1
73
0
Order By: Relevance
“…Data on person-level confounding variables (eg, reading speed and cognitive skills) were unavailable; adjusting for these variables, as well as item-level variables (eg, item complexity and length), could also improve the signal-to-noise ratio of the data through a richer statistical model 28,52–56,5861. Nevertheless, the direct use of the total amount of time taken on an assessment (ie, the raw completion time) had been found to have utility in previous work,12,37,6265 including the identification of aberrant answering 8,21,57…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on person-level confounding variables (eg, reading speed and cognitive skills) were unavailable; adjusting for these variables, as well as item-level variables (eg, item complexity and length), could also improve the signal-to-noise ratio of the data through a richer statistical model 28,52–56,5861. Nevertheless, the direct use of the total amount of time taken on an assessment (ie, the raw completion time) had been found to have utility in previous work,12,37,6265 including the identification of aberrant answering 8,21,57…”
Section: Discussionmentioning
confidence: 99%
“…In the context of educational testing, van der Linden and van Krimpen-Stoop noted that an individual’s response times are distinct from his/her answers; therefore, the response times may provide additional information about an individual’s level of aberrant responding that cannot be gleaned from the answer choices themselves 11. In a general assessment context, unduly fast responses may signify aberrant response behavior, for example, that an individual is responding carelessly in an effort to complete the assessment as quickly as possible, or is mechanically “faking good” in his/her responses, without deep consideration of the most accurate answer, when it is a simple matter to do so 8,1321. On the other hand, unduly slow responses may also signify aberrant response behavior, for example, an individual who takes an unduly long time to provide responses may be doing so because he/she is thoroughly assessing the answer choices to determine which is the most socially desirable, when making such a determination is not trivial 2224.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that giving warnings can effectively reduce careless responses. Explicit warning instructions such as “…responding without much effort will be flagged for low‐quality data” (Ward & Pond, ) and “…responding without much effort would result in loss of credits” (Huang et al, ) were shown to increase quality in responses. Because survey respondents who read the attention check can tell it is a “trap”, it signifies that the researchers are flagging low‐quality data, a function that resembles what a warning basically does.…”
Section: Overall Discussionmentioning
confidence: 99%
“…Researchers' use of attention checks may vary slightly, but they converge on two major forms. Perhaps the most popular form of attention check is instructed‐response items (see Bowling et al, ; Meade & Craig, ; Ward & Pond, ), which are items embedded in a scale with an obvious correct answer. The earlier example—“please select four for this item” and “please select moderately inaccurate for this item” (Huang, Curran, Keeney, Poposki, & DeShon, )—are common instructed‐response items.…”
Section: Introductionmentioning
confidence: 99%
“…Bowling, Huang, Bragg, Khazon, Liu, & Blackmore, ). In three studies, we use social psychological theories to develop and test three prevention strategies (Ward & Pond III, ) related to increasing respondent motivation to respond carefully. Study 1 presented control, scripted, or video‐recorded instructions designed to increase the social influence of survey administrators on survey participants.…”
mentioning
confidence: 99%